Assessing equity and sustainability of water allocation in Colombia. Issue 9 (2nd September 2017) - Roa-García, María Cecilia; Brown, Sandra
ABSTRACT: Based on the national database of 28, 104 water rights (concessions) granted in Colombia, this paper presents an analysis of how the principles of equity and sustainability are reflected in water allocation. Concessions appear to be an exclusionary mechanism since only a minority of small water users have concessions and the distribution of water volumes among those who have them is extremely inequitable. The 2009 Gini coefficient calculated for water concessions granted for agriculture was 0.90 compared with the rural land Gini of 0.88 (both indicators grouping holdings under the same entity). More than half of the Colombian departments have a higher Gini coefficient for water than for land, suggesting that water rights are at least as unequally distributed as land, in one of the most inequitable countries in Latin America. Water allocated to domestic, agriculture and hydropower use indicates a lack of consistency of water allocation criteria across regions. The volumetric and administrative attributes of water allocation in Colombia do not account for environmental flows or the concerns of marginalised groups of society that have limited access to the mechanism. Water allocation as a technical task, with limited transparency and secluded from public scrutiny, does not contribute to the solution of increasing water-related conflicts.